Get motivated! overcome any obstacle, achieve any goal, and accecelerate your success with motivational DNA - Lowe, Tamara (New York Doubleday, 2009)
Drawing on years of research and thousands of interviews, a motivational expert explains why some people are more motivated than others and how each individual can unleash his or her inner drive to identify and implement a motivational code to achieve success in every aspect of one's personal and professional life
The four laws of motivation -- What motivates you? -- The success strategies of highly motivated achievers -- Motivating people to improve their performance -- How producers produce -- The relationship secrets of connectors -- Developing the laser-sharp focus of stabilizers -- How to gain the bounce-back confidence of variables -- What internals know about the meaning of life -- Why externals succeed financially -- Tips and techniques for motivating young children -- Keys to helping kids achieve academic success -- How to motivate teens and young adults -- Start strong -- Sustain the action -- Finish first
Includes bibliographical references (p. 283-286) and index
1
Keywords: Leadership; Motivation (Psychology); Sucsses